Vilas Rurais: uma política pública de desenvolvimento e seu impacto na vida dos trabalhadores rurais volantes - Esser, Jovir Vicentini (2005)
This paper aimed to evaluate the impact of the Rural Village Program, as development public policy, in the lives of settlers, especially of the seasonal rural worker. In the context of rural development public policies, which was considered a unprecedented program in the country, Rural Villages implanted in the state of Paraná between 1995 and 2003 had as main recipient seasonal rural workers (S.R.W.), settling them in rural lots measuring an average of 5,000 m² near urban areas and in regions with a demand for temporary hand labor aiming to improve their live conditions. At first, it is shown the situation of the national agriculture issue from the point of view of some theorists, and its aggravation due to some Public Policies, such as the Rural Credit, that collaborated to the formation of a working category widely known as bóia fria (Day Laborer). It refers to the Rural Village Program, a sub-component of the 12 Month Paraná Project, emphasizing the process and implantation strategies giving emphasis to the Western Region of Paraná. According to acquired data, it was established that, although the main beneficiaries were the S.R.W., only 20% of the settled families had as landowner one of their workers. To achieve this proposed work objective a study was conduct on the case of Rural Villages in the cities of Corbélia and Anahy, where the impact of the Program in the life of the settlers was identified, specifically in the lives of the S.R.W. It was concluded that, even though the objective initially proposed of settling 60,000 families throughout the State was not reached, and some of the basic prerequisites defined by the Program were not abided, the evaluation was that if there was no significant change in economic terms, in the aspect of quality of life in loco ,through interviews with villagers, deep transformation was observed with the increasing in the families self steam and satisfaction in general, as far as having their own house and productive subsistence land. For an effective improvement on socioeconomic conditions, the Rural Villages still need income generating and technical assistance projects directed to non-qualified hand labor, such as day laborer. It is also possible, through the Rural Village experiences, to acquire larger areas by identifying those families that had shown capability in exploring agriculture, settling them in land financed by the Federal government s Rural Credit Program.